BRIDGING THE REGULATORY DIVIDE: ENSURING SAFETY AND EQUITY IN WEARABLE HEALTH TECHNOLOGIES - Toshmatova Visolakhon Ikrom kizi (Modern American Journals, 2025)
Wearable medical devices are becoming common tools for health monitoring and therapy, offering personalized and preventive care. However, their rapid growth outpaces legal regulation, creating a gap that threatens patient safety and equity in healthcare. This article examines international regulatory approaches, key issues of safety and data protection, and the accessibility of such technologies for different population groups. Successful regulatory examples illustrate effective strategies for safeguarding user rights. The conclusion stresses a balanced approach: strict oversight of safety and privacy while fostering innovation and ensuring equal access to wearable medical technologies.
Keywords: Wearable medical devices; regulation; safety; privacy; equity; accessibility; health data.